The study of industrialised building system, the implementation barriers of pm2 advance building system : a case study in Perlis - Ahmad Mikail Ahmad Nadzri (School of Environmental Engineering, University Malaysia Perlis, 2016)
The study is about the Industrialised Building System (IBS), The Implementation Barriers of PM2 Advance Building System. The study is made to determine the hindrance occurred using the IBS technique of PM2 panel. The objectives of the research are to study the level of awareness of usage of PM2 panel among the players in the construction project, to assess the problems arise in the usage and the implementation PM2 panel system and to give suggestion and recommendation to improve the PM2 panel system. The variables for this study are the knowledge among the project personnel, skills of local and foreign labourers, component supplier and the guidelines and building codes. Thirty respondents are sampled for this research. The method chosen for this research is survey. The survey is carried out by two ways including interviews and distribution of questionnaire among the targeted respondents. About twenty seven respondents have answered the questionnaire given in the survey conducted. The respondents are among the staff of the company involve in the construction in Perlis. They are from varies background which includes engineer, assistant engineer, quantity surveyor, technician, project manager, support staff and many more. The questionnaire answered are analyse using International Business Machines Statistical Package for the Social Sciences (IBM SPSS) version 23. The result shown that the main barriers to implement PM2 panel are basic knowledge of IBS, the cost and time of construction.